Effect of rennet on buffalo cheese microbiota, taste and flavor - Angela M. I. Montone; Angelo Citro; Germana Colarusso; Francesca Garofalo; Rubina Paradiso; Giorgia Borriello; Domenico Vecchio; Federico Capuano (Revista Científica)
Rennet is a critical element that allows the coagulation of milk caseins, the basic process of producing cheese. Traditional cheeses (Traditional Agri-food Products - PAT) are generally produced using artisanal animal rennet. The type of rennet used for cheese making, jointly with several other factors, influences the flavor and aroma of dairy products. In this study, we focused exclusively on rennet’s role in developing aromas and flavors, highlighting different tastes depending on the type of rennet used in cheesemaking. Buffalo milk was used to produce cheeses through a single cheesemaking session, where the only difference was the rennet used: commercial calf or artisanal lamb. Cheeses were stored and analyzed monthly at T0, T30, T60, and T90. Microbiota characterization (NGS technology) was performed on all samples, jointly with microbiological and sensory analysis (ISO 11035:1994). The microbiological analysis highlighted differences mainly in quantifying total bacteria count and acid lactic bacteria at T0, significantly higher in cheeses from calf rennet. Furthermore, at T60, a general reduction of all microbiological parameters in cheese based on lamb rennet was observed. The Microbiota analysis showed significant microbiological changes during the seasoning in the same product (α diversity) and between the two products obtained from industrial and artisanal rennet (β diversity). Regarding the sensory analysis, all the judges evaluated the cheeses based on lamb rennet as more appreciable due to their intense flavors and aroma. The study results confirmed the role of lamb rennet in developing flavor in buffalo cheese and, consequently, suggests a larger use of this rennet to obtain cheeses with a particular and typical taste based on buffalo milk.